Deficient intakes of energy and macronutrients in Pakistani female students assessed by composite samples method - Ali Khan Khattak, Muhammad Muzaffar; Khan, M.N. (Asian Network for Scientific Information, 2009)
The main purpose of the study was to compare the energy and macronutrients intakes by composite sample method. Duplicate food samples for seven days i.e., breakfast, lunch and dinner and whatever else ate during the week were analyzed for macronutrients consumption. Twenty female students were registered from the female hostel of the NWFP, Agricultural University Peshawar Pakistan. Age, weight, height and skin folds of the students were recorded on the day of the registration. From the anthropometry Basal Metabolic Index (BMI) was determined. The composite food samples were analyzed for protein, carbohydrates and fats. The energy values were determined by multiplying the daily eaten protein, carbohydrates and fats with 4, 4 and 9, respectively. The mean values of energy and macronutrients intakes were compared with the norms as appropriate. The energy and protein intakes were lower by -29.34% and protein intake was higher by 42.65% compared with American Dietetic Association (ADA). Similarly, compared to the WHO/FAO values the energy was lower -30.57 and protein was higher by 43.29, respectively. The energy contribution was higher from protein by 151% and lower from carbohydrates and fats by -28.35 and 23.43%, respectively. This study suggests that students are having deficient or imbalance energy intakes from macronutrients and are at the risk of malnutrition.